The Neural Correlates of Optimistic and Depressive Tendencies of Self-Evaluations and Resting-State Default Mode Network - Wu, Jinfeng; Dong, Debo; Jackson, Todd; Wang, Yu; Huang, Junfeng; Chen, Hong (Frontiers in Human Neuroscience, 2015)
Abstract: Unrealistic optimism is common among people making self-evaluations while reduced optimism has been linked to increased depressive symptoms. Given the importance of optimism for adaptive functioning, surprisingly little is known about resting brain states underlying optimistic and depressive tendencies. In the current study, two resting-state indices were used to examine the neural correlates of default mode network (DMN) and optimistic and depressive tendencies in a nonclinical young adult sample. Due to the self-referential nature of DMN, the analysis was constrained within it. Across different indices, bilateral superior frontal gyri of the dorsolateral prefrontal cortex (DLPFC) and bilateral superior medial frontal gyri of the dorsal medial prefrontal cortex (DMPFC) play a key role in maintaining optimistic tendencies of spontaneous self-evaluations. Conversely, decreased activity in DLPFC and bilateral medial orbitofrontal cortices (OFC) are related to accentuated depressive symptoms. Together, results highlight the pivotal roles of the DLPFC and DMPFC in mediating valences of self-referential content.